Progress of Research on Exosomes in the Protection Against Ischemic Brain Injury - Kang, Xianhui; Zuo, Ziyi; Hong, Wandong; Tang, Hongli; Geng, Wujun (Frontiers in Neuroscience, 2019)
Exosomes, as a type of extracellular vesicle (EV), are lipid bilayer vesicles 20-100 nm in diameter that can cross the blood-brain barrier. Exosomes are important transport vesicles in the human body that participate in many conduction pathways and play an important physiological role. Because of their high biocompatibility and low immunogenicity and toxicity, exosomes have attracted increasing attention as an attractive drug delivery system. This article reviews the relevant studies that have shown that exosomes play an important role in protective mechanisms against ischemic brain injury.